Jesus, psychological type and conflict: A study in biblical hermeneutics applying the reader perspective and SIFT approach to Mark 11:11–21 - Francis, Leslie J. (HTS teologiese studies, 2016)
The Marcan account of Jesus riding into Jerusalem on a donkey, cursing the fig tree and overturning the tables of the money changers in the temple provides a classic scriptural reference point for a Christian discussion of conflict. Drawing on psychological type theory and on the reader perspective proposed by the SIFT (sensing, intuition, feeling and thinking) approach to biblical hermeneutics and liturgical preaching, this study tests the theory that different psychological types will interpret this classic passage differently. Data collected in two residential programmes concerned with Christianity and conflict from type-aware participants confirmed characteristic differences between the approaches of sensing types and intuitive types and between the approaches of thinking types and feeling types.